Feasibility and Acceptability of the Use of Patient-Reported Outcome Measures in the Delivery of Nurse-Led, Supportive Care to Women With Cervical Cancer. Issue 4 (July 2017) - Kotronoulas, Grigorios; O'Brien, Fran; Simpson, Mhairi F.; Maguire, Roma
Abstract : Purpose/Aims: Patient-reported outcome measures (PROMs) can be effectively used to uncover the unmet needs of women with cervical cancer for supportive care. Our aim was to explore the feasibility and acceptability of PROM-driven, nurse-led consultations to enhance delivery of supportive care to women with cervical cancer during active anticancer treatment. Design: A 2-phased, mixed-method prospective study was conducted. Main research variables included feasibility and acceptability parameters of the trialed intervention. Methods: Preconsultation PROM data were collected during 3 consecutive monthly consultations and used by the gynecology cancers nurse specialist (CNS) to deliver personalized supportive care. The problem checklist and Cervical Cancer Concerns Questionnaire were used to aid data collection. Findings: Because of considerable recruitment challenges, a recruitment rate of 27% (3/11 patients) was achieved. Two patients completed all 3 study assessments. Seven in-clinic patient assessments were performed over 6 months. The study participants praised the opportunity for dedicated time for patients to raise concerns and for the CNS to provide sensitive and personalized support. Conclusion: Women with cervical cancer perceive important benefits from participating in PROM-driven, time-protected sessions with their CNS. Our findings provide tentative evidence to support the feasibility and acceptability of this intervention model and warrant future confirmation. Implications for Practice: Use of patient-reported outcome measures (PROMs) to identify the unmet needs of women with cervical cancer is acceptable and must be implemented from the point of diagnosis. Cancer nurse specialists (CNS) are receptive to and able to act on PROM information, rendering them key professionals in addressing the supportive care needs of people with cancer. Women with cervical cancer perceive important benefits from participating in PROM-driven, time-protected, and private sessions with their CNS.